Pengaruh ROE, ROA, dan DER Terhadap Harga Saham Pada Perusahaan Sektor Perbankan Yang Terdaftar di BEI Periode 2023-2024 - Ilham, Arifin; Herdiansyah, Ary Dwi Putra; Jannah, Elvi Nikmatul; Manda, Gusganda Suria (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2025)
This research aims to analyze how Return on Equity (ROE), Return on Assets (ROA), and Debt to Equity Ratio (DER) influence stock prices in banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2024 period. This study uses a quantitative approach and relies on secondary data sourced from the annual financial reports of banking companies and publications from the Financial Services Authority (OJK). The sample in this study includes 20 banking companies chosen through purposive sampling. The findings show that collectively, the variables ROE, ROA, and DER have a significant influence on stock prices. Partially, ROE has a considerable positive impact on stock prices, whereas ROA and DER each show a significant negative impact. The coefficient of determination (R²) of 0.595 shows that the three variables explain 59.5% of the variation in stock prices, while the remaining 40.5% is influenced by other factors beyond the model. These results are expected to provide useful insights for investors and banking management on how financial ratios relate to stock price movements.